Unveiling new abilities of actinobacteria: Proficiency in the bioremoval of the emerging contaminant ivermectin - Victoria Guadalupe González Holc; María Alejandra Small; Gonzalo Arnau; Claudia Susana Benimeli; Juan Daniel Aparicio; Marta Alejandra Polti (Chemosphere, 2026)

Intraspecific Variation in Thermal Performance Suggests the Presence of Range‐Edge Divergence and Phenotypic Compensation of Northern Individuals in an Introduced Species - Giuseppe Garlaschè; David Drolet; Cyrena Riley; Daniel Small; Kimberly L. Howland; Christopher W. McKindsey; Piero Calosi (Global Ecology and Biogeography, 2025)
Aim Intraspecific variation in functional traits may indicate adaptation to environmental gradients and is crucial to understanding species distributions and range dynamics. We tested the hypotheses that: (1) thermal performance of Littorina littorea follows a countergradient cline, reflecting compensation in northern individuals and (2) local differentiation occurs at the range limits of its non‐native Atlantic distribution. Location Atlantic coast of North America, 46 to 51°N. Time Period 2022. Major Taxa Studied Intertidal gastropods (Littorinidae). Methods Snails from 10 locations, spanning 10° of latitude and approximately 1700 km, were exposed to a gradient of 12 temperatures in the laboratory, and survival, growth, feeding, metabolic rate and heat tolerance were measured. Thermal performance curves obtained were compared and used to calculate performance parameters: that is, thermal optimum, maximum performance and thermal breadth. Results Snails from the northern and southern range edges exhibited a gradual divergence in growth performance parameters relative to central populations. Snails from colder northern locations exhibited greater survival, feeding rate and heat tolerance when exposed to higher temperatures. Main Conclusions The divergent local variation in the growth of individuals from range edges may reflect a stronger selective pressure occurring at the species range limits. In contrast, the clinal countergradient patterns observed for survival, feeding rate and heat tolerance suggest that individuals from northern locations have a greater acclimation capacity to compensate for stronger environmental fluctuations associated with higher latitudes. Our findings suggest that the greater acclimation capacity of northern populations could give them an advantage with the progression of climate changes, supporting the likelihood of a poleward range shift. By revealing trait‐specific trends of variation, our study demonstrates the importance of investigating multiple traits along a wide range of acclimation temperatures in individuals from locations across broad latitudinal gradients to uncover patterns of phenotypic change that would otherwise remain unexplored.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Application of Sentinel-1 InSAR to monitor tailings dams and predict geotechnical instability: practical considerations based on case study insights - Nahyan M. Rana; Keith B. Delaney; Stephen G. Evans; Evan Deane; Andy Small; Daniel A. M. Adria; Scott McDougall; Negar Ghahramani; W. Andy Take (Bulletin of Engineering Geology and the Environment, 2024)
Tailings storage facilities (TSFs) impound mining waste behind dams to ensure public safety, but failure incidents have prompted calls for more robust monitoring programs. Satellite-based interferometric synthetic aperture radar (InSAR) has grown in popularity due to its ability to remotely detect millimeter-scale displacements in most urban and some natural terrains. However, there remains a limited understanding of whether InSAR can be as accurate or representative as on-the-ground instruments, whether failures can be predicted in advance using InSAR, and what variables govern the quality and reliability of InSAR results. To address these gaps, we analyze open-source, medium-resolution Sentinel-1 data to undertake a ground-truth assessment at a test site and a forensic analysis of five failure cases. We use a commercial software with an automated Persistent Scatterer (PS) workflow (SARScape Analytics) for all case study sites except one and a proprietary algorithm (SqueeSAR) with a dual PS and Distributed Scatterer (DS) algorithm for the ground-truth site and one forensic case. The main goal is to deliver practical insights regarding the influence of algorithm/satellite selection, environmental conditions, site activity, coherence thresholds, satellite-dam geometry, and failure modes. We conclude that Sentinel-1 InSAR can serve as a hazard-screening tool to help guide where to undertake targeted investigations; however, most potential failure modes may not exhibit InSAR-detectable accelerations that could assist with time-of-failure prediction in real time. As such, long-term monitoring programs should ideally be integrated with a combination of remote sensing and field instrumentation to best support engineering practice and judgment.

Correction to: Evaluation of a multi-model approach to estimate leaf wetness duration: an essential input for disease alert systems - Andre B. Gama; Daniel Perondi; Megan M. Dewdney; Clyde W. Fraisse; Ian M. Small; Natalia A. Peres (Theoretical and Applied Climatology, 2022)

Evaluation of a multi-model approach to estimate leaf wetness duration: an essential input for disease alert systems - Andre B. Gama; Daniel Perondi; Megan M. Dewdney; Clyde W. Fraisse; Ian M. Small; Natalia A. Peres (Theoretical and Applied Climatology, 2022)

Hot and cold flavors of southern California’s Santa Ana winds: their causes, trends, and links with wildfire - Alexander Gershunov; Janin Guzman Morales; Benjamin Hatchett; Kristen Guirguis; Rosana Aguilera; Tamara Shulgina; John T. Abatzoglou; Daniel Cayan; David Pierce; Park Williams; Ivory Small; Rachel Clemesha; et al. (Climate Dynamics, 2021)
Santa Ana winds (SAWs) are associated with anomalous temperatures in coastal Southern California (SoCal). As dry air flows over SoCal’s coastal ranges on its way from the elevated Great Basin down to sea level, all SAWs warm adiabatically. Many but not all SAWs produce coastal heat events. The strongest regionally averaged SAWs tend to be cold. In fact, some of the hottest and coldest observed temperatures in coastal SoCal are linked to SAWs. We show that hot and cold SAWs are produced by distinct synoptic dynamics. High-amplitude anticyclonic flow around a blocking high pressure aloft anchored at the California coast produces hot SAWs. Cold SAWs result from anticyclonic Rossby wave breaking over the northwestern U.S. Hot SAWs are preceded by warming in the Great Basin and dry conditions across the Southwestern U.S. Precipitation over the Southwest, including SoCal, and snow accumulation in the Great Basin usually precede cold SAWs. Both SAW flavors, but especially the hot SAWs, yield low relative humidity at the coast. Although cold SAWs tend to be associated with the strongest winds, hot SAWs tend to last longer and preferentially favor wildfire growth. Historically, out of large (> 100 acres) SAW-spread wildfires, 90% were associated with hot SAWs, accounting for 95% of burned area. As health impacts of SAW-driven coastal fall, winter and spring heat waves and impacts of smoke from wildfires have been recently identified, our results have implications for designing early warning systems. The long-term warming trend in coastal temperatures associated with SAWs is focused on January–March, when hot and cold SAW frequency and temperature intensity have been increasing and decreasing, respectively, over our 71-year record.

On the control of subantarctic stratification by the ocean circulation - R. Justin Small; Alice K. DuVivier; Daniel B. Whitt; Matthew C. Long; Ian Grooms; William G. Large (Climate Dynamics, 2021)

Population genomics of the filarial nematode parasite Wuchereria bancrofti from mosquitoes - Scott T. Small; Lisa J. Reimer; Daniel J. Tisch; Christopher L. King; Bruce M. Christensen; Peter M. Siba; James W. Kazura; David Serre; Peter A. Zimmerman (Molecular Ecology, 2016)
Wuchereria bancrofti is a parasitic nematode and the primary cause of lymphatic filariasis – a disease specific to humans. W. bancrofti currently infects over 90 million people throughout the tropics and has been acknowledged by the world health organization as a vulnerable parasite. Current research has focused primarily on the clinical manifestations of disease and little is known about the evolutionary history of W. bancrofti . To improve upon knowledge of the evolutionary history of W. bancrofti , we whole genome sequenced 13 W. bancrofti larvae. We circumvent many of the difficulties of multiple infections by sampling larvae directly from mosquitoes that were experimentally inoculated with infected blood. To begin, we used whole genome data to reconstruct the historical population size. Our results support a history of fluctuating population sizes that can be correlated with human migration and fluctuating mosquito abundances. Next, we reconstructed the putative pedigree of W. bancrofti worms within an infection using the kinship coefficient. We deduced that there are full‐sib and half‐sib relationships residing within the same larval cohort. Through combined analysis of the mitochondrial and nuclear genomes we concluded that this is likely a results of polyandrous mating, the first time reported for W. bancrofti . Lastly, we scanned the genomes for signatures of natural selection. Annotation of putative selected regions identified proteins that may have aided in a parasitic life style or may have evolved to protect against current drug treatments. We discuss our results in the greater context of understanding the biology of an animal with a unique life history and ecology.

The sensitivity of the early benthic juvenile stage of the European lobster Homarus gammarus (L.) to elevated pCO2 and temperature - Daniel P. Small; Piero Calosi; Dominic Boothroyd; Stephen Widdicombe; John I. Spicer (Marine Biology, 2016)

The roles of oxygen and ammonia in the symbiotic relationship between the spotted salamander Ambystoma maculatum and the green alga Oophila amblystomatis during embryonic development - Daniel P. Small; R. Scott Bennett; Cory D. Bishop (Symbiosis, 2014)

Hybridization between two gartersnake species (Thamnophis) of conservation concern: a threat or an important natural interaction? - John S. Placyk; Benjamin M. Fitzpatrick; Gary S. Casper; Randall L. Small; R. Graham Reynolds; Daniel W. A. Noble; Ronald J. Brooks; Gordon M. Burghardt (Conservation Genetics, 2012)

Derivation of Man-1 and Man-2 research grade human embryonic stem cell lines - Maria V. Camarasa; Robbie W. Kerr; Sharon F. Sneddon; Nicola Bates; Lisa Shaw; Rachel A. Oldershaw; Fiona Small; Melissa A. Baxter; Tristan R. Mckay; Daniel R. Brison; Susan J. Kimber (In Vitro Cellular & Developmental Biology - Animal, 2010)

The pharmacokinetics and pharmacodynamics of prasugrel in healthy Chinese, Japanese, and Korean subjects compared with healthy Caucasian subjects - David S. Small; Prajakti Kothare; Eunice Yuen; D. Richard Lachno; Ying G. Li; Kenneth J. Winters; Nagy A. Farid; Lan Ni; Joseph A. Jakubowski; Daniel E. Salazar; Vivian T. Thieu; Christopher D. Payne (European Journal of Clinical Pharmacology, 2010)

Population pharmacokinetics and pharmacodynamics of prasugrel and clopidogrel in aspirin-treated patients with stable coronary artery disease - C. Steven Ernest; David S. Small; Shashank Rohatagi; Daniel E. Salazar; Lars Wallentin; Kenneth J. Winters; Rebecca E. Wrishko (Journal of Pharmacokinetics and Pharmacodynamics, 2008)

Structure and expression of several bean (Phaseolus vulgaris) nuclear transfer RNA genes: relevance to the process of tRNA import into plant mitochondria - Daniel Ramamonjisoa; Sabine Kauffmann; Nathalie Choisne; Laurence Maréchal-Drouard; Gaynor Green; Henri Wintz; Ian Small; André Dietrich (Plant Molecular Biology, 1998)